2021
DOI: 10.4103/ijo.ijo_2192_20
|View full text |Cite
|
Sign up to set email alerts
|

Anterior chamber intraocular lens - An effective alternative in traumatic and surgical aphakia in the era of scleral-fixated intraocular lens

Abstract: Purpose: To evaluate outcomes of anterior chamber intraocular lens (ACIOL) implantation with vitrectomy in eyes with surgical or traumatic aphakia, and subluxated or dislocated lens. Methods: In this retrospective study, we evaluated patients who underwent pars plans vitrectomy with ACIOL implantation from April 2016 to March 2019. Patients with minimum follow-up period of 1 year and operated by single surgeon were included. Ophthalmic history, indication for surgery, B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…[23] Mahapatra et al reported that no patient developed corneal decompensation in ACIOL implantation. [15] In our study. Mean ACD was measured at 3,03 ± 0.29 mm.…”
Section: Resultsmentioning
confidence: 60%
“…[23] Mahapatra et al reported that no patient developed corneal decompensation in ACIOL implantation. [15] In our study. Mean ACD was measured at 3,03 ± 0.29 mm.…”
Section: Resultsmentioning
confidence: 60%
“…The initial situation (including the degree of capsular bag and iris defects) must be taken into account for choosing the type of correction. Anterior chamber IOL has the advantage of small learning curve, faster surgical time, and less complications like vitreous hemorrhage and suture erosion compared to scleral-fixated IOLs [ 3 , 4 ]. In cases of both, capsular and iris deficiency, glued IOL with aniridia IOL, or iridoplasty with glued IOLs showed good functional and anatomical results [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thank you for the interest in our article entitled “Anterior chamber intraocular lens - An effective alternative in traumatic and surgical aphakia in the era of scleral-fixated intraocular lens” published in the Indian Journal of Ophthalmology. [ 1 2 ] Here are clarifications to the issues raised by you.…”
mentioning
confidence: 99%